The NOURISHED randomised controlled trial comparing mentalisation-based treatment for eating disorders (MBT-ED) with specialist supportive clinical management (SSCM-ED) for patients with eating disorders and symptoms of borderline personality disorder. Issue 1 (December 2016) - Robinson, Paul; Hellier, Jennifer; Barrett, Barbara; Barzdaitiene, Daiva; Bateman, Anthony; Bogaardt, Alexandra; Clare, Ajay; Somers, Nadia; O'Callaghan, Aine; Goldsmith, Kimberley; Kern, Nikola; Schmidt, Ulrike; et al.
Abstract Background In this multi-centre randomized controlled trial (RCT) we compared modified mentalisation-based treatment (MBT-ED) to specialist supportive clinical management (SSCM-ED) in patients with eating disorders (EDs) and borderline personality disorder symptoms (BPD). This group of patients presents complex challenges to clinical services, and a treatment which addresses their multiple problems has the potential to improve outcome. MBT has been shown to be effective in improving outcome in patients with BPD, but its use has not been reported in ED. Methods Sixty-eight eligible participants were randomised to MBT-ED or SSCM-ED. The primary outcome measure was the global score on the Eating Disorder Examination. Secondary outcomes included measures of BPD symptoms (the Zanarini Rating Scale for Borderline Personality Disorder), general psychiatric state, quality of life and service utilisation. Participants were assessed at baseline and at 6, 12 and 18 months after randomisation. Analysis was performed using linear mixed models. Results Only 15 participants (22 %) completed the 18 month follow-up. Early drop-out occurred significantly more in the SSCM-ED group. Drop-out did not vary with treatment model later in therapy and was sometimes attributed to participants moving away. There was higher drop–out amongst smokers and those with higher neuroticism scores. 47.1 % of participants in the MBT-ED arm and 37.1 % in the SSCM-ED arm attended at least 50 % of therapy sessions offered. Amongst those remaining in the trial, at 12 and 18 months MBT-ED was associated with a greater reduction in Shape Concern and Weight Concern in the Eating Disorder Examination compared to SSCM-ED. At 6, 12 and 18 months there was a decline of ED and BPD symptoms in both groups combined. Ten participants were reported as having had adverse events during the trial, mostly self-harm, and there was one death, attributed as 'unexplained' by the coroner. Conclusions The high drop-out rate made interpretation of the results difficult. Greater involvement of research staff in clinical management might have improved compliance with both therapy and research assessment. MBT-ED may have had an impact on core body image psychopathology. Trial registration Current Controlled Trials:ISRCTN51304415 . Registered on 19 April 2011.